The Effect of Deep Bite on Periodontal Status of Anterior Teeth - Sulistiawati, Sulistiawati; Awalia, Hema; Zakyah, Akhyar Dyni; Putri, Julia Anjani (Indonesian Dental Association, 2020)
Introduction: Deep bite is a malocclusion in which the vertical overlap of the mandibular incisor exceeds 4 mm when the teeth are positioned in centric occlusion. Traumatic deep bite, a condition in which deep bite has caused traumatic occlusion, can exert pressure that increases inflammation and damage to the periodontal tissue. The prolonged pressure produces injury to the gingival surface and periodontal tissues of the opposing teeth. Objective: To determine the effect of deep bite on the periodontal status of anterior teeth. Methods: A cross-sectional analytic study of 44 subjects who were divided into two groups of 22. Subjects gave informed consent and underwent an examination of periodontal status for gingival recession, probing depth, and clinical attachment loss. Dental impressions were taken for the measurement of deep bite. Data were then analyzed using univariate and multivariate analysis. Result: There were significant differences between the normal and deep bite group for the presence and severity of gingival recession, probing depth, and clinical attachment loss (p <0.05). Conclusion: There is an association between deep bite and periodontal status (gingival recession, probing depth, and clinical attachment loss) of anterior teeth.